An Omnidirectional, High Power Density Magneto–Mechano–Electric Energy Harvester Using PNN–PZT Piezoceramic Operating in Decoupling Bending Mode - Wei Peng; Bin Wang; Jianglei Chang; Zhen Liu; Genshui Wang; Zhi Cheng; Liang Ma; Shuxiang Dong (Advanced Energy & Sustainability Research)
Magneo‐mechano‐electric energy harvesters (MME‐EHs) capture stray magnetic and weak vibration energy from power lines and vehicles. However, efficiently harvesting microenergy from randomly oriented stray magnetic fields remains challenging. We propose a novel MME‐EH featuring two cross‐arranged, piezoceramic‐metal laminated beams with tip magnetic masses. Using Pb(Ni1/3Nb2/3)O3‐Pb(Zr0.3Ti0.7)O3‐LiNbO3(PNN–PZT–LN) ceramic with a high piezoelectric charge coefficient (e33) and operating in decoupled diagonal symmetric bending modes, this design efficiently harvests omnidirectional stray magnetic energy. The high e33 enables significant output current, while the decoupling design avoids interference between two cross‐beams, and diagonal symmetry bending modes with a simple support at the central node can dramatically decrease the clamping energy losses. The portable MME‐EH generates a record‐high output power of 13.3 mWavg under a weak 2Oe magnetic field at 50 Hz. More importantly, its output power changes less than 22% as the magnetic field direction varies from 0° to 360°, demonstrating omnidirectional energy‐capturing capability. The harvested energy successfully powers a multisensor Internet of Things system for real‐time environmental monitoring, highlighting the potential of high e33 materials and decoupling strategies for efficient energy harvesting from weak, randomly oriented stray magnetic fields.